Does Transparency of Central Banks Produce Multiple Equilibria on Currency Markets? - Axel Lindner (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
A recent strand of literature (see Morris and Shin 2001) shows that multiple equilibria in models of markets for pegged currencies vanish if there is slightly diverse information between traders. It is known that this approach works only if there is not too precise common knowledge in the market. This has led to the conclusion that central banks should try to avoid making their information common knowledge. We present a model in which more transparency of the central bank means better private information, because each trader utilizes public information according to her own private information. Thus, transparency makes multiple equilibria less likely.
urn:nbn:de:gbv:3:2-20439
Keywords: 330; Devisenmarkt; Währungskrise; Wechselkurspolitik; Staatliche Information; Währungsspekulation; Asymmetrische Information; Theorie; Gleichgewicht